2022
DOI: 10.1108/jkm-07-2021-0527
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge hiding behavior in higher education institutions: a scientometric analysis and systematic literature review approach

Abstract: Purpose The purpose of this paper is to systematically review knowledge hiding (KH) behavior in higher education institutions (HEIs). KH is regarded as an unethical and antisocial behavior by many scholars, which should not be prevalent in HEIs. Design/methodology/approach A two-phase analysis through quantitative scientometric analysis and qualitative systematic literature review method through the preferred reporting items for systematic reviews and meta-analyses (PRISMA) model was applied. In phase 1,174 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 91 publications
1
28
0
Order By: Relevance
“…The findings supported our prediction and reveal that PC positively moderates the link between employees' SSB and KH (H4). Moreover, the combined effect of individual characteristics (i.e., SSB and PC) on KH is found significant, hence complemented recent research confirming that individual characteristics are important predictors for KH behavior (Hernaus et al, 2018;Fauzi, 2022). These findings successfully contribute to the literature of personality as we analyzed how some personality traits (i.e., SSB and PC) of employees affect their KH behavior.…”
Section: Discussionsupporting
confidence: 78%
“…The findings supported our prediction and reveal that PC positively moderates the link between employees' SSB and KH (H4). Moreover, the combined effect of individual characteristics (i.e., SSB and PC) on KH is found significant, hence complemented recent research confirming that individual characteristics are important predictors for KH behavior (Hernaus et al, 2018;Fauzi, 2022). These findings successfully contribute to the literature of personality as we analyzed how some personality traits (i.e., SSB and PC) of employees affect their KH behavior.…”
Section: Discussionsupporting
confidence: 78%
“…For instance, government-based organizations, multinational corporations or family own-based organizations would gain substantial insight into KH. Empirical or review studies can be conducted, such as a recent review by Fauzi (2022) that reviewed KH in higher education, providing meaningful insight on this behavior among academics, administrators and Evaluation of critical research streams students. Furthermore, studies on individual personality traits can be further developed, as currently, only one study adopted openness to experience traits within its framework (Banagou et al, 2021).…”
Section: Implications and Future Work 51 Theoretical Implicationsmentioning
confidence: 99%
“…Third, this review conceptualizes all relevant counterproductive behavior related to KS. Despite the fact that the terminology of KH is broader, which others have defined the behavior as knowledge hoarding, knowledge disengagement, partial KS and knowledge sabotage (Wu, 2020;Fauzi, 2022), KH is the most adapted terminology as it reflects the difference within the three dimensions of hiding, representing a holistic view of the counterproductive behavior. This review will reveal and understand previous scholars' studies in the KH phenomenon, focusing on team KH behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The same pattern holds for individuals who seek information to improve their job performance: if they are strongly driven to learn, they will be able to learn more and faster. A recent study on knowledge hiding recommended investigating it as a moderator between innovation antecedents and outcomes, especially among knowledge workers ( Fauzi, 2022 ). Another recent research in the Chinese context was conducted on knowledge hiding and innovative behaviors and reported that knowledge hiding has the potential to play a moderating role in the innovation environment to hinder the success of any innovative activity ( Chen et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%